FACTORS OF EXPRESSION OF MEANING IN FOLK PROVERBS (Bulletin of Innovative Research, 2026)
This article theoretically studies the expressive aspects of the meaning found in folk proverbs. It is also proven on the basis of examples that the process of human cognition of the world is reflected in proverbs and sayings, that is, that their conclusions are hidden in the content of proverbs. It is skillfully illustrated that the complex of life and experiences of our people finds its expression in the lines of the proverb, which can be called a substitute for human life and experiences, and therefore proverbs are simple, concise and beautiful, and simplicity is covered with the gloss of content and acquires beauty